EUROPEAN FUNDS AUDIT IN ROMANIA - ANCA SIMINA POPESCU (Annals of the University of Petrosani: Economics, 2015)
To become a a net beneficiary of EU funds, Romania must ensure an absorption rate as higher as it can. The appreciation of the these funds' management and formulating opinions in support of improving the absorption of European funds in the future can be done with the audit because it is a guarantee for good performance by our country, but also by public authorities, of commitments which they have undertaken.